Well-differentiated cerebellum in an ovarian mature cystic teratoma: a case report and review of the literature - Ahmed AlEssa; Hassan H. AlAhmadi; Ayesha Ahmed; Abdulatif AlMousa; Nasreen G. Hamadeh; Yasir A. Hassan Farah (Journal of Medical Case Reports, 2022)
Abstract Background Mature teratoma is the most common germ cell tumor as it represents 95% of germ cell tumors. Although common in children and young adults, ovarian teratoma can occur at any age. Mature teratomas are composed of mature tissues representing elements derived from more than one embryonic germ layer (ectoderm, mesoderm, and endoderm), with ectodermal derivatives being the usual predominant component; however, the finding of a well-differentiated cerebellum is extremely rare. Case presentation A 20-year-old Saudi female presented to the emergency department with severe abdominal pain of 1-day duration. Pelvic ultrasound showed a large ovoid- to bilobed-shaped cystic pelvic structure extending to the lower abdomen. The patient underwent left ovarian cystectomy. Microscopic examination showed a cyst wall with skin tissue, including adnexal structures (sebaceous glands), a well-differentiated cerebellum, and mature glial tissue. After extensive sampling, no immature component was identified. Thus, the final diagnosis of a mature cystic teratoma with well-differentiated cerebellum was established. The patient was well postoperatively and was discharged in a stable condition. Conclusion We report this case of well-differentiated cerebellum within ovarian teratoma to expand the pool of cases reported in literature of this extremely rare entity, as only 22 cases with such findings have been reported in literature to the best of our knowledge. This finding poses a diagnostic challenge to the pathologist due to its rarity and its similarity to immature teratoma. We thus emphasize that thorough sampling of ovarian teratoma is of paramount importance and to keep the aforementioned diagnosis in mind and not confuse it with immature elements, especially in intraoperative consultation and frozen sections.